United in Diversity? An Empirical Investigation on Europe's Regional Social Capital - Fabian Braeseman; Fabian Stephany (Agenda Austria, 2017)
Aiming to explain the European divide with respect to social and political values, scholars in the past have relied on a simplified four- (or even two-) dimensional regime model which tranches the continent according to the social capacities of its inhabitants. This ,,cartography“ of ,,Social Europe“ proves to be outdated by the presented findings. In this work, we apply a factor analysis model to the most commonly used approximations of social capital on the European Social Survey. The analysis shows that three distinct dimensions of social capital measures are important in Europe: additionally to generalised social capital, which is usually approximated by generalised trust, there is one dimension of civic engagement and one of communitarian values. This distinction leads to a new social landscape of Europe, which highlights the relevance of considering regional and cross-border clusters in all relevant social capital dimensions. A hierarchical multi-level model that controls for individual and regional characteristics emphasises the importance of the spatial clustering in Europe with respect to social capital. In addition, we explore, as a novelty in social capital literature, a classification tree to model generalized trust. The results of the non-parametric model reveal that Protestantism and education are good benchmarks to classify trust on an individual level. Based on these findings we argue for the necessity of policies with a regional focus that take the different sub-national structures of social capacity in Europe into account.
Keywords: C33; C38; D70; Z13; 330; classification trees; factor analysis; social capital; multi-level modeling